Running Performance and Position is Not Related to Decision-Making Accuracy in Referees - Riiser, Amund; Andersen, Vidar; Sæterbakken, Atle; Ylvisaker, Einar; Moe, Vegard Fusche (Sports Medicine International Open, 2019)
We aimed to assess if running performance is related to decision-making accuracy in referees. We also investigated the relationships between movement, position, decision-making and time of infringement. The study included 347 free kicks and penalties awarded during all 15 home field matches for one team in the Norwegian top league. Movement and position were measured by a radio-based positioning system, and two external experts analysed the video clips. The referees made the correct decision in 98% of the assessed foul situations. There were no associations between the correctness and running speed at the time of the infringements or total distance accumulated during the 30 s prior to the infringement (p>0.08). Decision-making accuracy was not associated with the referees’ position in relation to the infringements (p=0.82) or the area where the infringements occurred (p=0.28). Most foul play incidents were sanctioned in the central area of the field (84%) where the distance to the infringements was shorter (13.4 m, 95% CI 12.8–14.0) than in the lateral areas (21.9 m, 95% CI 20.4–23.4). Norwegian top referees were practically always right when they interfered, possess the necessary fitness to avoid fatigue that would influence decision-making accuracy, and maintain adequate positional ability throughout the matches.
Keywords: match analysis; soccer; football